A phosphotyrosine switch regulates organic cation transporters - Jason A. Sprowl (Nature Portfolio, 2016)
Organic cation transporters are important drug transporters that influence therapeutic outcomes. Here, the authors find that these transporters are regulated by tyrosine phosphorylation and propose that tyrosine kinase inhibitors can influence drug transporter function through post-translational mechanisms.